A narrative review of recent developments in osseointegration and anti-corrosion of titanium dental implants with nano surface - Hoda Ghodrati; Ali Goodarzi; Mohammad Golrokhian; Farnaz Fattahi; Reza Mahmoudi Anzabi; Meysam Mohammadikhah; Saiedeh Sadeghi; Sabah Mirhadi (Bone Reports)
Titanium (Ti) is widely acknowledged as the top choice for constructing dental implants because of its remarkable biocompatibility and biomechanical characteristics. Its rapid oxidation in the presence of oxygen forms a protective titanium dioxide (TiO2) layer on the implants’ surface, ensuring resistance to corrosion. This thin oxide layer plays a crucial role in establishing the favorable biocompatibility of Ti implants. However, under mechanical loading conditions, the integrity of the TiO2 layer can be compromised through the dynamic interactions between the implant and bone tissue, leading to localized damage and subsequent corrosion. This corrosion weakens the implant and may result in the release of metallic particles or ions into the surrounding living tissues. Consequently, corrosion serves as a potential catalyst for the emergence of malfunctions in dental implants, whether biological or mechanical in nature. To address this issue, extensive research has focused on nanoscale surface modifications aimed at enhancing the durability and resistance to chemical and electrochemical changes exhibited by dental implants made from Ti. Hence, this narrative review specifically examines nano surface modifications of titanium dental implants, focusing on their effects on corrosion resistance, biomechanical performance, and osseointegration, distinguishing it from other reviews that address broader aspects of titanium implants or general corrosion mechanisms.